30 Lumateperone (ITI-007) for the Treatment of Schizophrenia: Overview of Placebo-Controlled Clinical Trials and an Open-label Safety Switching Study. (12th March 2019) - Vanover, Kimberly; Glass, Steven; Kozauer, Susan; Saillard, Jelena; Sanchez, Juan; Weingart, Michal; Mates, Sharon; Satlin, Andrew; Davis, Robert
Abstract: Background: Lumateperone is a first-in-class agent in development for schizophrenia that acts synergistically through serotonergic, dopaminergic and glutamatergic systems. Lumateperone is a potent 5-HT2A antagonist, a mesolimbic/mesocortical dopamine phosphoprotein modulator (DPPM) with pre-synaptic partial agonist and post-synaptic antagonist activity at D2, a glutamate GluN2B receptor phosphoprotein modulator with D1-dependent enhancement of both NMDA and AMPA currents via the mTOR protein pathway and an inhibitor of serotonin reuptake. Methods: Lumateperone was evaluated in 3 controlled clinical trials to evaluate efficacy in patients with acute schizophrenia. The primary endpoint was change from baseline on the PANSS total score compared to placebo. In Study '005, 335 patients were randomized to receive ITI-007 60mg or 120mg, risperidone 4mg (active control) or placebo QAM for 4weeks. In Study '301, 450 patients were randomized to receive ITI-007 60mg or 40mg, or placebo QAM for 4weeks. In Study '302, 696 patients were randomized to receive ITI-007 60mg or 20mg, risperidone 4mg (active control) or placebo QAM for 6weeks. Also, an open-label safety switching study was conducted in which 302 patients with stable schizophrenia were switched from standard-of-care (SOC) antipsychotics and treated for 6weeks with lumateperone QPM and then switched back to SOC. Results: In Studies '005 and '301, lumateperone (60mg ITI-007) met the primary endpoint with statistically significant superior efficacy over placebo at Day 28. In Study '302, neither dose of lumateperone separated from placebo on the primary endpoint; a high placebo response was observed in this study. Across all 3 efficacy trials, lumateperone improved symptoms of schizophrenia with the same trajectory and same magnitude of improvement from baseline to endpoint on the PANSS total score. Lumateperone was well-tolerated with a favorable safety profile in all studies. In the two studies with risperidone included as an active control, lumateperone was statistically significantly better than risperidone on key safety and tolerability measures. In the open-label safety switching study statistically significant improvements from SOC were observed in body weight, cardiometabolic and endocrine parameters worsened again when switched back to SOC medication. In this study, symptoms of schizophrenia generally remained stable or improved. Greater improvements were observed in subgroups of patients with elevated symptomatology (comorbid symptoms of depression and those with prominent negative symptoms). Discussion: Lumateperone represents a novel approach to the treatment of schizophrenia with a favorable safety profile in clinical trials. The lack of cardiometabolic and motor safety issues presents a safety profile differentiated from standard-of-care antipsychotic therapy. Funding Acknowledgements: Intra-Cellular Therapies, Inc.